2002
DOI: 10.1149/1.1518988
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-Coated Si as a Lithium-Ion Battery Anode Material

Abstract: Carbon-coated Si has been prepared by a thermal vapor decomposition method. Its electrochemical performance has been investigated by charge/discharge tests, cyclic voltammetric experiments, differential scanning calorimetry, and 7 Li-nuclear magnetic resonance, etc. This kind of material demonstrates good electrochemical performance as an anode material for lithium-ion batteries. The improvement in the electrochemical performance of Si is mainly attributed to the effect of carbon coating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
291
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 421 publications
(308 citation statements)
references
References 13 publications
6
291
1
Order By: Relevance
“…This is probably because the carbon layer is less active for the reductive decomposition of the electrolyte solution than Si surface. 27 Though it was found that Q irr can be effectively reduced by the carboncoating, it should be reduced much more for practical applications. As for the reversible (discharge) capacity, the pristine Si-LP, Si-LP@C(600°C), and Si-LP@C(700°C) had similar initial discharge capacities (25002800 mAh g ¹1 ).…”
Section: ¹1mentioning
confidence: 99%
See 2 more Smart Citations
“…This is probably because the carbon layer is less active for the reductive decomposition of the electrolyte solution than Si surface. 27 Though it was found that Q irr can be effectively reduced by the carboncoating, it should be reduced much more for practical applications. As for the reversible (discharge) capacity, the pristine Si-LP, Si-LP@C(600°C), and Si-LP@C(700°C) had similar initial discharge capacities (25002800 mAh g ¹1 ).…”
Section: ¹1mentioning
confidence: 99%
“…In previous studies, 2226 we have reported that the use of Si thin flakes, Si Leaf Powder μ (Si-LP, Oike & Co., Ltd.), is effective for improving the cycleability by relaxation of the stress due to the volume changes. However, the high Q irr still remained in the first cycle, which is caused by decomposition of the electrolyte solution 27 as well as irreversible reduction of thin oxide layer on the Si-LP surface during the first charging process as:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the practical application of Si to LIBs is quite challenging because Si is associated with significant volume changes which arise during lithium insertion and extraction, which can hasten mechanical fracture of the electrode, cause a loss of electrical conduction paths, and results in continuous electrolyte decomposition at the active surface when exposed by the cracking of Si during cycling, as depicted in Fig. 1 [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…43,44 However, this design still possesses three flaws. First, it does not consider the volume changes of silicon during electrochemical reactions.…”
mentioning
confidence: 99%